2019
DOI: 10.1016/j.bbi.2018.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GPR55 induces neuroprotection of hippocampal neurogenesis and immune responses of neural stem cells following chronic, systemic inflammation

Abstract: New neurons are continuously produced by neural stem cells (NSCs) within the adult hippocampus. Numerous diseases, including major depressive disorder and HIV-1 associated neurocognitive disorder, are associated with decreased rates of adult neurogenesis. A hallmark of these conditions is a chronic release of neuroinflammatory mediators by activated resident glia. Recent studies have shown a neuroprotective role on NSCs of cannabinoid receptor activation. Yet, little is known about the effects of GPR55, a cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 90 publications
1
44
0
Order By: Relevance
“…According to available data, effects of the GPR55 receptor stimulation in the inflammatory processes may be bi-directional, i.e. pro-inflammatory ( Chiurchiu et al, 2015 ) or anti-inflammatory ( Hill et al, 2019 ), depending on the study design and experimental conditions. In the in vitro studies by Chiurchiu et al (2015) , O-1602 enhanced production of IL-12 and TNF-α in lipopolysaccharide-activated monocytes and negatively affected its ability to phagocytose, whereas in the in vitro studies by Hill et al (2019) , exposure to O-1602 suppressed pro-inflammatory responses within neural stem cells during their insult with IL-1β.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to available data, effects of the GPR55 receptor stimulation in the inflammatory processes may be bi-directional, i.e. pro-inflammatory ( Chiurchiu et al, 2015 ) or anti-inflammatory ( Hill et al, 2019 ), depending on the study design and experimental conditions. In the in vitro studies by Chiurchiu et al (2015) , O-1602 enhanced production of IL-12 and TNF-α in lipopolysaccharide-activated monocytes and negatively affected its ability to phagocytose, whereas in the in vitro studies by Hill et al (2019) , exposure to O-1602 suppressed pro-inflammatory responses within neural stem cells during their insult with IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…pro-inflammatory ( Chiurchiu et al, 2015 ) or anti-inflammatory ( Hill et al, 2019 ), depending on the study design and experimental conditions. In the in vitro studies by Chiurchiu et al (2015) , O-1602 enhanced production of IL-12 and TNF-α in lipopolysaccharide-activated monocytes and negatively affected its ability to phagocytose, whereas in the in vitro studies by Hill et al (2019) , exposure to O-1602 suppressed pro-inflammatory responses within neural stem cells during their insult with IL-1β. Furthermore, animals genetically deprived of GPR55 receptors presented prolonged inflammatory response (with elevated IL-1β, IL-6, TNF-α values) after chronic low-level administration of lipopolysaccharide ( Hill et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, no data is available as to the eCB-specific downstream signaling pathways recruited by cannabinoid receptors that would be facilitating neuronal survival and differentiation, despite some approximations in this regard (Luján et al, 2018 ). Furthermore, there also remain some unexplored CBD mechanisms with potential pro-neurogenic properties, such as GPR55 activation for coping reduction of neurogenesis in response to inflammatory insults (Hill et al, 2019 ). Noteworthy, a protective interaction involving neuroinflammation processes has been already observed, showing that CBD-mediated activation of PPARγ is associated with increased neurogenic activity, as well as reduced reactive gliosis, in the granule cell layer of the hippocampal DG (Esposito et al, 2011 ).…”
Section: Promoting Neurogenesis With Cannabidiolmentioning
confidence: 99%
“…A recent study showed that the cannabinoid system can modulate NSP proliferation and have a neuroprotective role, rescuing hippocampal neurogenesis during HIV-1 neurotoxic insults [125,126]. Activating a candidate cannabinoid receptor, GPR55, suppressed the pro-inflammatory responses of IL-1β treatment on adult rat hippocampal NSCs in vitro, rescuing the negative effects of IL-1β on neurogenesis [127].…”
Section: Interleukin-1 and Hippocampal Neurogenesismentioning
confidence: 99%